Using a trauma informed practice framework to enhance understanding of and identify support strategies for behavioural difficulties in young people with Prader-Willi syndrome. (March 2021) - Schofield, Cara; Martin, Karen; S Choong, Catherine; Gibson, David; Skoss, Rachel; Downs, Jenny
Highlights: A TIP framework can be used to map support for young people with complex needs. Novel domains specific to PWS aided the development of support strategies. Strategies supporting individuals with PWS encourage dialogue between environments. Abstract: Background: Behavioural support for young people with Prader-Willi syndrome (PWS) is necessary in home and school environments. The Trauma Informed Practice (TIP) framework has been used to support young people with complex behavioural needs in school settings. Aims: To identify parent and professional perspectives on behavioural challenges experienced by young people with PWS and strategies for supports, to inform understanding of how they are aligned with the TIP framework. Method: Semi-structured interviews were conducted with eight families with a 12–21 year old child with PWS, four clinicians and two teachers to investigate the contexts and mechanisms associated with challenging, calm and productive behaviours. Data were analysed using directed content analysis, using TIP principles as a framework. Results: Strategies to support young people with PWS aligned with the four overarching TIP Principles: Empowerment, voice and choice ; Creating safe environments ; Creating a collaborative environment; and Trustworthiness and transparency . Additional Novel domains included: Behavioural underpinnings, Modifying environments and Supporting family capacity . Conclusion: These novel domains can be used to supplement the TIP framework for guidance on how to support young people with PWS. Health implications: Development and implementation of strategies to reduce behavioural difficulties in young people with PWS through positive support mechanisms could improve function and social engagement within their families and communities.